Continuous feeding of spent ammonium sulphite liquor improves the production and saccharification performance of cellulase by Penicillium oxalicum. (December 2017) - Han, Xiaolong; Liu, Guodong; Song, Wenxia; Qin, Yuqi; Qu, Yinbo
Highlights: Fermentation with continuous feeding SASL improved cellulase production. The maximum FPase reached 17.66 U/mL using a multi-stage feeding strategy. Comparative proteomic analysis showed that SASL induced cellulases synthesis. The SASL-induced cellulase could hydrolyze ammonium sulphite pulp efficiently. Abstract: Spent ammonium sulphite liquor (SASL) is the main effluent from the ammonium sulphite pulping process, and contains amounts of lignocellulosic oligomers, monosaccharides and ammonium salts. The effect of continuous SASL-feeding on cellulase production by Penicillium oxalicum was studied. With a rate-varying feeding strategy, the maximal filter paper enzyme (FPase) activity reached 17.66 U/mL at 144 h, and the specific FPase activity increased from 1.74 U/mg (without SASL) to 2.40 U/mg. Accordingly, the glucan hydrolysis conversion of delignified corn cob residue by the enzymes from continuous SASL-feeding fermentation was significantly higher than that without SASL at equal protein loadings. Comparative proteomic analysis demonstrated that the proteins involved in lignocellulose degradation were specifically up-regulated in the crude cellulase with SASL-feeding. The obtained crude enzyme was efficient in the hydrolysis of pulping products, with a glucan conversion of 81.87% achieved after 72 h saccharification of ammonium sulphite pulp.